Implementasi Prinsip Keadilan dalam Penyelesaian Perselisihan Ketenagakerjaan di Pengadilan - Ridho Sadillah Ahmad; Hermastita Sekar Ayu Asmara (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
Settlement of labor disputes in court requires the application of a clear and uniform concept of justice. For labor disputes to be resolved fairly, courts must ensure that procedures are carried out in a manner that upholds the rights of the parties to the dispute, is fair and non-discriminatory. The main causes of conflict between workers and management include different viewpoints between workers and employers, employment contracts, rights and responsibilities, and competing interests. Improving dispute resolution processes and ensuring fairness can increase the effectiveness of the employment law system. Writing about a phenomenon using data and presenting facts and data factually and accurately based on case analysis and related matters is known as writing quantitative analysis. This writing is also accompanied by a discussion of court cases which function to uphold the principles of justice at the Industrial Relations Court. The current legal system offers both litigation and non-litigation means for resolving disputes. These mechanisms include industrial relations courts using bipartite negotiations, mediation and arbitration in accordance with law number 2 of 2004. The main problem is the high time and costs involved in resolving labor disputes, even with a clear legal framework. Before starting negotiations, labor organizations must also fulfill several prerequisites. The state plays an important role in encouraging the peaceful resolution of conflicts and fostering a peaceful environment between employers and workers. The social peace of industrial society is significantly affected by injustice in labor relations, in addition to the individuals affected. If justice is not achieved at every stage of industrial relations, disharmony will continue. It is important to improve the quality of procedural law, dispute resolution systems, and legal awareness among all parties.